Asymmetric [4+2] annulations to construct norcamphor scaffolds with 2-cyclopentenone via double amine–thiol catalysis. Issue 9 (15th January 2018) - Yang, Qian-Qian; Xiao, Wei; Du, Wei; Ouyang, Qin; Chen, Ying-Chun
Abstract : A double catalytic system combining chiral amine and 2-mercaptobenzoic acid is applied for α′, β-regioselective [4+2] annulations of 2-cyclopentenone with diverse activated alkenes. Abstract : An efficient double catalytic system, combining chiral amine and 2-mercaptobenzoic acid, is applied for α′, β-regioselective [4+2] annulations of 2-cyclopentenone with a diversity of activated alkenes, constructing multifunctional chiral bicycle[2, 2, 1]heptane scaffolds in good to excellent yields and enantioselectivities. In comparison with the traditional cross-dienamine species between 2-cyclopentenone and chiral amine, the interrupted enamine intermediate containing a covalently linked thiol catalyst shows significantly improved reactivity.